Marked Clinical Improvement of Psoriasis Vulgaris with Methotrexate: A Case Report with 75% PASI Reduction - Widya Gabriella Manurung; Kristo Alberto Nababan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Psoriasis is an immune-mediated chronic, recurrent, systemic inflammatory disease induced by the combination of hereditary and environmental factors. The etiology of this disease involves many factors, including genetics, immunology, and the environment. Clinically, psoriasis vulgaris is characterized by the presence of reddish plaques with thick, symmetrically distributed squama mainly in the predilection areas. In moderate to severe cases, systemic therapy such as phototherapy, systemic anti-inflammatory agents, or biologic treatments is required, with topical therapy serving as an adjunct. Methotrexate is one of the effective systemic treatment options for severe psoriasis, either as monotherapy or in combination regimens. This case report aims to demonstrate the clinical efficacy of methotrexate in the management of moderate-to-severe psoriasis vulgaris. We report a case of a 37-year-old male presenting with scaly reddish skin thickening accompanied by itching all over the body. Clinical and histopathological examination confirmed the diagnosis of Psoriasis Vulgaris and treated with methotrexate. After a period of regular weekly methotrexate administration and monitoring, the patient achieved a 75% reduction in the Psoriasis Area and Severity Index (PASI), indicating significant therapeutic response. This case highlights the efficacy of methotrexate as a cost-effective and accessible treatment option for achieving substantial disease control in psoriasis vulgaris.